Active suspension system design for railway vehicles transporting sensitive goods and hazardous materials - Mohd Anwar, Zawawi (2008)
This project presents the dynamic modelling and control of railway vehicle active suspension systems. The vehicle types selected for this study are the two-axle and bogie-based railway vehicle. The performances of the passive and active suspensions are simulated and compared as the vehicle moves on straight and curved track. The input to the system is the curve radius and its corresponding cant angle. The curving performance was evaluated from the lateral and yaw displacement of the wheelset, bogie and vehicle body. The wheelset arrangement for active suspension selected in this study is the actively-stabilized wheelset with rotary actuator and the wheelset with independently- rotating wheels. The optimal controller was chosen to control the lateral and yaw deflections of the vehicle. The comparison between the two-axle (without bogie) and bogie-based vehicles, as well as the active suspension with actively stabilized wheelset and independently rotating wheels are illustrated to highlight the advantages and disadvantages of each vehicle type and active suspension options. The active suspension of railway vehicle with independent rotating wheelset showed a better curving performance than the one with solid axle wheelset as the wheels were no longer connected to each other.